Life Cycle Assessment of Concrete Pavement Rehabilitation: A Romanian Case Study - Pleșcan, Costel; Barta, Melinda; Maxineasa, Sebastian George; Pleșcan, Elena-Loredana (MDPI AG, 2022)
The most well-known and used evaluation system to determine the life cycle of a product, is the life cycle assessment (LCA). In Europe, the use of the life cycle assessment (LCA) to assess the environmental performance of products is becoming commonplace, which is why substantial efforts have been made in the last two decades to develop new life cycle assessment (LCA) methodologies and software. This paper evaluates the life cycle assessment (LCA) for the rehabilitation of a national road sector in Romania. The biggest ecological problem facing mankind is the effect of global warming and climate change associated with this phenomenon, due to the increase of the concentration of pollutants to the atmosphere, and this paper presents the results of the life cycle assessment (LCA) based on a cradle-to-gate approach. For this case study, were used three rehabilitation alternatives. These alternatives and the existing pavement structure were analysed using the GaBi software, Ganzheitlichen Bilanzierung (German for holistic balancing), to assess the environmental impact of global warming, the stratospheric impact of ozone, and the impact on human health. The results obtained in this study illustrate the importance of a life cycle assessment approach for evaluating the sustainability for different designs and for the construction of road rehabilitation options.